Synthetic method of amphiphilic quasi-conjugated molecule

By linking highly reactive reactive groups on the conjugated skeleton and using high-efficiency chemical reactions such as click reaction, efficient copolymerization and functional regulation of hydrophilic components and conjugated skeleton are achieved, the problem of limitations in the performance of existing photosensitizers is solved, and the precise regulation and efficient synthesis of photophysical properties are achieved.

CN119912676AActive Publication Date: 2025-05-02HEBEI UNIV OF TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510029052.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-05-02
Estimated Expiration
2045-01-08

AI Technical Summary

Technical Problem

Existing photosensitizers have limitations in performance, such as fixation of energy conversion efficiency and lack of flexibility in functional regulation, resulting in potential damage to healthy tissue during treatment.

Method used

By linking branches with high-reactive reactive groups at the end or side of the conjugated framework, efficient copolymerization and functional regulation of hydrophilic components and the conjugated framework can be achieved, efficient chemical reactions such as click reactions improve the reactivity and selectivity of molecules, and optimize the self-assembly behavior of molecules by adjusting the reaction solvent and conditions.

Benefits of technology

It significantly improves the synthesis efficiency of materials, and realizes the precise regulation of photophysical properties, improves the accuracy and controllability of treatment, and is suitable for areas such as photothermal therapy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119912676A_ABST
    Figure CN119912676A_ABST
Patent Text Reader

Abstract

The invention provides a synthetic method of an amphiphilic quasi-conjugated molecule. High-activity reactive groups such as an azide group, a triple bond group and other reactive groups are grafted at the tail end or side chain of the conjugated skeleton, so that efficient copolymerization and functional regulation of a hydrophilic component and the conjugated skeleton are realized. The reactivity and selectivity of molecules are remarkably improved by utilizing efficient chemical reactions such as click reaction and the like. Meanwhile, by adjusting reaction solvents and conditions, optimizing molecular self-assembly behaviors and regulating molecular weight, chain length and structure of molecules, particle size, morphology and assembly characteristics of the nanoparticles are accurately controlled, so that synthesis efficiency is improved, and photophysical properties are accurately regulated. The technology not only improves the synthesis efficiency of the material, but also provides a new strategy and thought for the design and application of functional materials such as photoelectric materials, drug delivery materials and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material synthesis, and in particular relates to a method for synthesizing amphiphilic quasi-conjugated molecules and a technology for regulating the photophysical properties thereof. Background Art

[0002] With the continuous progress in fields such as medicine, chemistry and pharmacy, the development of new treatment methods has become an important task to improve health levels. Traditional diagnosis and drug development usually face challenges such as long cycles, high costs, and limited success rates, which to a certain extent restrict the improvement of treatment effects. Therefore, there is an urgent need to explore and develop new strategies that can replace or supplement traditional drug treatments. In this context, regulating the synthesis of specific molecules and their photophysical functions provides a new direction for achieving efficient and precise treatment. However, many traditional photosensitizers currently have limitations in performance, such as fixed energy conversion efficiency and lack of flexibility in functional regulation, which makes it difficult to avoid potential damage to healthy tissues during treatment. Therefore, the development of more precise and controllable treatment technologies based on innovations in molecular design and photophysical function regulation has important clinical application value. Summary of the invention

[0003] To solve the above problems, the present invention proposes an innovative method for synthesizing amphiphilic quasi-conjugated molecules and a method for regulating their functions. By grafting highly active reactive groups, such as azide groups, triple bond groups and other reactive groups, at the ends or side chains of the conjugated skeleton, efficient copolymerization and functional regulation of the hydrophilic component and the conjugated skeleton are achieved. By utilizing efficient chemical reactions such as click reactions, the reactivity and selectivity of the molecules are significantly improved. At the same time, by adjusting the reaction solvent and conditions, the molecular self-assembly behavior is optimized, and by regulating the molecular weight, chain length and structure of the molecules, the particle size, morphology and assembly characteristics of the nanoparticles are precisely controlled, thereby improving the synthesis efficiency and accurately regulating the photophysical properties. This technology not only improves the synthesis efficiency of the material, but also provides new strategies and ideas for the design and application of functional materials such as optoelectronics and drug delivery.

[0004] The method for synthesizing an amphiphilic quasi-conjugated molecule provided by the present invention comprises the following steps: copolymerizing a conjugated structure molecule represented by formula I with a hydrophilic macromolecule represented by formula II to obtain a conjugated polymer, namely, an amphiphilic quasi-conjugated molecule;

[0005]

[0006] In Formula I, Any of the following groups: (R is H or C1-C 10 Straight or branched alkyl), (R=-C m H 2m - ),

[0007] is any of the following groups: hydrogen, -N3, -NH2; n = an integer of 1-10; m = an integer of 1-10; may be any of the following groups: hydrogen, alkynyl, thiol, carboxyl, and aldehyde; and Cannot be H at the same time;

[0008] In formula II, The same as or different from ○, at least one of which is any one of an azido group, an alkynyl group, a thiol group, a carboxyl group and an aldehyde group, and the other can be C1-C 10 Alkoxy group, such as methoxy group; n represents an integer of 10-50.

[0009] In the conjugated structure molecule shown in Formula I, by constructing a narrow band gap donor-acceptor skeleton, the quinone or diradical properties of the acceptor are enhanced, thereby reducing the band gap and achieving near-infrared light response. The aggregation state is regulated by stimulus-responsive molecules, thereby regulating the light absorption capacity and excited state energy level. In addition, the intermolecular charge transfer characteristics adjust the absorption wavelength by optimizing the frontier orbital energy level, and combine the aggregation-induced emission characteristics to achieve precise regulation of the light response. Groups that can undergo click reactions are also introduced into the molecular structure to enhance the functional regulation ability of the molecule.

[0010] Specifically, the conjugated structure molecule represented by the above formula I is any one of the following compounds:

[0011]

[0012] The hydrophilic macromolecule shown in Formula II is endowed with good solubility and self-assembly ability by the combination of polyethylene glycol (PEG) group and conjugated skeleton. Highly active reactive groups such as azide group, triple bond group, thiol group, amino group, etc. are grafted at the end of PEG group, which has high reactivity and can carry out various chemical reactions (such as click reaction, Markel addition reaction, etc.) to achieve functionalization and regulation.

[0013] Specifically, the hydrophilic macromolecule represented by the above formula II is any one of the following compounds:

[0014]

[0015] Specifically, the synthesis method of the amphiphilic quasi-conjugated molecule is: a hydrophilic macromolecule containing an azide group and a conjugated structure molecule containing an alkyne group are subjected to a click reaction;

[0016] Alternatively, a hydrophilic macromolecule containing an alkyne group is subjected to a click reaction with a conjugated structure molecule containing an azide group to obtain an amphiphilic quasi-conjugated molecule.

[0017] Furthermore, the synthesis method of the amphiphilic quasi-conjugated molecule is as follows: in an inert atmosphere and in the presence of an inorganic salt, a hydrophilic macromolecule containing an azide group and a conjugated structure molecule containing an alkyne group undergo a click reaction.

[0018] Or in an inert atmosphere, in the presence of an inorganic salt, a hydrophilic macromolecule containing an alkynyl group undergoes a click reaction with a conjugated structure molecule containing an azide group to obtain an amphiphilic quasi-conjugated molecule;

[0019] Wherein, the inorganic salt may be at least one of cuprous iodide and cuprous bromide;

[0020] The molar fraction of the hydrophilic macromolecule can be 0.075 to 1.5 parts;

[0021] The molar fraction of the conjugated structure molecule can be 0.100 to 0.380 parts;

[0022] The inorganic salt may be added in an amount of 0.075 to 1.5 parts by mole;

[0023] Specifically, the molar ratio of the hydrophilic macromolecule to the conjugated structure molecule and the inorganic salt can be 4:1:4;

[0024] The click reaction may be carried out at a temperature of 25-80°C, specifically 75°C, and for a time of 24-72h, specifically 48h.

[0025] The amphiphilic quasi-conjugated molecules (amphiphilic conjugated polymers) prepared by the above-mentioned synthesis method also fall within the protection scope of the present invention.

[0026] Specifically, the amphiphilic quasi-conjugated molecule is one of the following polymers:

[0027]

[0028] The amphiphilic conjugated polymer can be dispersed spontaneously in an aqueous solution to form nanoparticles.

[0029] Nanoparticles prepared from the above-mentioned amphiphilic conjugated polymers also fall within the protection scope of the present invention.

[0030] The nanoparticles have a particle size range of 100-300 nanometers and have excellent ultraviolet absorption performance, with an ultraviolet absorption peak in the range of 600-900 nanometers. Under the irradiation of light corresponding to the absorption peak, the temperature of the nanoparticles can quickly rise to 40-80 degrees Celsius, thereby achieving effective photothermal conversion. Its photothermal conversion efficiency can reach 30-50%, showing a strong photothermal effect, and is suitable for fields such as photothermal therapy. The structural and functional characteristics of these nanoparticles make them have broad potential in biomedical applications.

[0031] The present invention also provides two methods for preparing the amphiphilic polymer nanoparticles.

[0032] First, solvent replacement method:

[0033] (1) dissolving an amphiphilic polymer in an organic solvent, and removing the organic solvent by vacuum distillation to form a thin film;

[0034] (2) adding the obtained film to ultrapure water to obtain an aqueous solution of nanoparticles by a self-assembly method;

[0035] (3) Treating the aqueous solution of the obtained nanoparticles by a dialysis method to obtain nanoparticles.

[0036] In step (1) of the above method, the organic solvent may specifically be chloroform, tetrahydrofuran, 1,4-dioxane, toluene, etc.;

[0037] The temperature used for vacuum distillation is 30-60°C and the pressure is 10-300 mmHg;

[0038] The thickness of the film formed is about 0.5-2mm;

[0039] In step (2) of the above method, the volume of ultrapure water may be 8-15 mL, specifically 10 mL;

[0040] In step (3) of the above method, the molecular weight cut-off of the dialysis bag used for dialysis is 3500 kDa.

[0041] Second, solvent replacement method:

[0042] (1) First, the amphiphilic polymer is dissolved in a small amount of organic solvent to form a uniform solution;

[0043] (2) rapidly adding the obtained solution into ultrapure water;

[0044] (3) allowing the organic solvent to interact with the solvent in the aqueous phase by stirring, ultrasonic treatment or other methods;

[0045] (4) Finally, the nanoparticles are separated from the organic solvent by evaporation or displacement of the solvent to form a stable aqueous dispersion, and the water is removed to obtain the nanoparticles.

[0046] In step (1) of the method, the organic solvent may be chloroform, tetrahydrofuran, etc., and the volume of the organic solvent may be 0.2-2 ml, specifically 0.5 ml;

[0047] In step (2) of the above method, the volume of ultrapure water may be 8-15 mL, specifically 10 mL.

[0048] The advantages of the present invention are:

[0049] 1. Simplified preparation process: adopts efficient and green preparation methods, reduces the use of harmful solvents, and has lower energy consumption and higher production efficiency, which is suitable for large-scale production.

[0050] 2. Controllable particle size and distribution: The particle size and distribution of polymers can be precisely controlled during the preparation process to ensure the stability and uniformity of the nanoparticles and meet the needs of different applications.

[0051] 3. Excellent biocompatibility: The amphiphilic structure enhances the application potential of the polymer in the biomedical field. It is suitable for drug carriers and gene therapy and has good biocompatibility and stability.

[0052] 4. The prepared nanoparticles have uniform morphology and stable structure, which effectively solves the problem of poor water solubility of conjugated polymers;

[0053] 5. This conjugated polymer has amphiphilic and self-assembly properties. After forming nanoparticles, it shows a spectral red shift and has a stronger photothermal effect. By modifying the hydrophilic side chain groups, it utilizes the hydrophobic effect to self-assemble into water-soluble photothermal effect nanomaterials.

[0054] 6. Adjustable electronic and optical properties: The quasi-conjugated structure gives it excellent electronic and optical properties, can adjust the band gap, improve charge transfer and stability, and is suitable for optoelectronic materials, sensors and other fields.

[0055] 7. Dual structural functionality: The polymer has an amphiphilic structure and can self-assemble or stably disperse between the aqueous phase and the oil phase, making it suitable for a variety of applications such as drug delivery and nanoparticle preparation. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] Figure 1 The synthetic route for preparing nanoparticles in Example 1 of the present invention is shown in FIG.

[0057] Figure 2 The ultraviolet absorption graph (a), infrared absorption graph (b), TEM graph (c), and particle size graph (d) of the nanoparticle 1-NP obtained in Example 1 of the present invention are shown.

[0058] Figure 3 This is a photothermal absorption diagram of the nanoparticles prepared in Example 1 of the present invention.

[0059] Figure 4 This is a synthetic route for preparing nanoparticles in Example 2 of the present invention.

[0060] Figure 5 The ultraviolet absorption graph (a), infrared absorption graph (b), TEM graph (c), and particle size graph (d) of the nanoparticles obtained in Example 2 of the present invention are shown.

[0061] Figure 6 This is the photothermal absorption diagram of IEG-NP prepared in Example 2 of the present invention.

[0062] Figure 7 This is a synthetic route for preparing nanoparticles in Example 3 of the present invention.

[0063] Figure 8 The ultraviolet absorption graph (a), infrared absorption graph (b), TEM graph (c), and particle size graph (d) of the nanoparticles prepared in Example 3 of the present invention.

[0064] Fig. 9 This is the photothermal absorption diagram of the nanoparticles prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0065] The present invention is further described in detail below in conjunction with specific embodiments, and the examples provided are only for illustrating the present invention, rather than for limiting the scope of the present invention. The examples provided below can be used as a guide for further improvements by those of ordinary skill in the art, and do not constitute a limitation of the present invention in any way.

[0066] The experimental methods in the following examples, unless otherwise specified, are all conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels.

[0067] Example 1. Synthesis of Conjugated Polymer 1

[0068] according to Figure 1 The synthetic route shown is for the preparation of conjugated polymer 1.

[0069] Specific operations include:

[0070] Synthesis of 9,9-dihexyl-9H-fluorene (Compound 1): A mixture of fluorene (1 g, 0.006 mol), iodohexane (2.8 g, 0.0132 mol) and sodium hydroxide (0.72 g, 0.018 mol) was placed in DMSO (7.2 mL) and stirred overnight at 90 °C under an inert atmosphere. After cooling to room temperature, the solution was poured into cold water, and the resulting mixture was extracted with dichloromethane (50 mL). The combined organic layer was washed with water, dried over anhydrous sodium sulfate overnight, filtered, and concentrated to dryness. The crude product was purified by silica gel column chromatography using petroleum ether as the eluent to obtain a colorless solid. 1H NMR(400MHz,Chloroform-d)δ7.67(d,J=7.2Hz,1H),7.60-7.43(m,2H),7.28(d, J=14.8Hz,4H),1.55(s,4H),1.26(s,4H),0.88(s,1H),0.07(s,1H),0.00(s,3H).

[0071] Synthesis of 2-bromo-9,9-dihexyl-9H-fluorene (Compound 2): 9,9-dihexyl-9H-fluorene (Compound 1) (13 g, 46 mmol) and NBS (8.25 g, 46 mmol) were mixed in acetone (50 mL) and stirred at 80 ° C for 3 h under nitrogen protection. After cooling to room temperature, the solution was poured into cold water, and the resulting mixture was extracted with dichloromethane (③500 mL). The combined organic layer was washed with water, dried over anhydrous sodium sulfate, filtered, and concentrated to dryness. The crude product was purified by silica gel short column chromatography using petroleum ether as eluent to obtain a colorless solid. 1H NMR(400MHz,Chloroform-d)δ7.95(s,1H),7.73(d,J=8.3Hz,1H),7.64(s,1H),7.59(s,2H),7.54(s,2H),7.47-7.38(m,3 H),7.26(s,3H),2.01-1.79(m,15H),1.55(s,3H),1.26(s,3H),1.20-0.93(m,47H),0.79(t,J=7.0Hz,23H),0.53(s,15H).

[0072] Synthesis of 2-bromo-9,9-dihexyl-7-iodo-9H-fluorene (Compound 3): 2-bromo-9,9-dihexyl-9H-fluorene (Compound 2) (15.4 g, 43 mmol), iodine (6.5 g, 25.8 mmol), concentrated sulfuric acid (2.3 mL), periodic acid (1.7 g, 25.8 mmol), and water (7.7 mL) were stirred at 60 ° C for 4 h in glacial acetic acid (74 mL). After cooling to room temperature, the solution was poured into ice-cold water containing a large amount of sodium sulfite, and the resulting mixture was extracted with dichloromethane (③100 mL). The combined organic phase was washed twice with water, dried over anhydrous sodium sulfate, and concentrated to dryness. The crude product was purified by short silica gel column chromatography using petroleum ether as the eluent to obtain a light yellow solid. 1HNMR(400MHz,Chloroform-d)δ7.67(s,1H),7.56(d,J=7.8Hz,1H),7.47(s,2H),7.32(s,3H) ,1.95(dt,J=11.7,5.3Hz,4H),1.22-0.94(m,14H),0.78(t,J=7.1Hz,7H),0.71-0.50(m,4H).

[0073] Synthesis of bromo-7-ethynyl-9,9-dihexyl-9H-fluorene (Compound 4): 2-bromo-9,9-dihexyl-7-iodo-9H-fluorene (Compound 3) (3.00 g, 6.21 mmol) was dissolved in NEt3 triethylamine (30 mL) and deoxygenated by 3 freeze pump-thaw cycles. The flask was purged with nitrogen. PdCl2(PPh3)2 (130 mg, 0.19 mmol), CuI (70 mg, 0.37 mmol) and trimethylsilyl acetylene (0.92 mL, 6.46 mmol) were added and stirred at room temperature for 6 h. The solvent was removed under reduced pressure and the residue was flash filtered through a silica gel column and eluted with petroleum ether. The solvent was removed to obtain a yellow solid. It was added to a mixture of deoxygenated CH2Cl2 and methanol (1:1, 30 mL). 1HNMR(400MHz,Chloroform-d)δ7.58(d,J=7.8Hz,1H),7.52(d,J=8.4Hz,1H), 7.45(d,J=6.2Hz,3H),7.41(s,1H),1.92(dd,J=11.4,5.5Hz,4H),1.51(s,1H), 1.43(s,1H),1.28(d,J=8.6Hz,3H),1.20-0.92(m,13H),0.87(dt,J=11.9,7.1H z, 2H), 0.78 (t, J = 7.2Hz, 6H), 0.56 (dq, J = 12.5, 6.7, 6.2Hz, 4H), 0.29 (s, 10H).

[0074] K2CO3 (1.72 g, 12.42 mmol) was added and stirred at room temperature for 5 h. The solvent was removed under vacuum, and alumina and silica gel column chromatography were performed in sequence. The residue was filtered. 1H NMR (400 MHz, Chloroform-d) δ7.61 (d, J = 7.9 Hz, 1H), 7.54 (d, J = 8.5 Hz, 1H), 7.51-7.41 (m, 4H), 7.26 (s, 3H), 3.15 (s, 1H), 2.06-1.81 (m, 5H), 1.55 (s, 5H), 1.26 (s, 4H), 1.18-0.95 (m, 14H), 0.87 (d, J = 7.6 Hz, 1H), 0.77 (t, J = 6.8 Hz, 7H), 0.55 (d, J = 14.4 Hz, 5H).

[0075] Synthesis of tributyl(2,3-dihydrothieno[3,4-b][1,4]dioxin-5-yl)tinane (Compound 5): Under argon protection, 3,4-ethylenedioxythiophene (8.45 g, 59.43 mmol) and anhydrous tetrahydrofuran (100 mL) were added to a 500 mL double-necked bottle in sequence. After the solution was cooled to -78°C, 26 mL of n-butyl lithium (62.4 mmol, 2.4 M) was added dropwise within 1 hour, and after stirring at this temperature for 1 hour, the temperature was raised to -20°C for reaction for 1 hour. The reaction system temperature was then lowered to -78°C and stirred for 30 minutes, and tributyltin chloride (21.28 g, 65.37 mmol) was added dropwise at this temperature within 30 minutes. After that, the reactants were stirred at -78°C for another hour, then slowly heated to room temperature and stirred overnight. After the reaction is completed, the mixture is poured into 100 mL of water and extracted with dichloromethane. The organic phase is washed with saturated brine and dried over anhydrous sodium sulfate for 24 h. The solvent is removed by reduced pressure distillation. The obtained product can be directly used for the next step without purification.

[0076] 5-(7-Ethynyl-9,9-dihexyl-9H-fluorene-2-yl)-2,3-dihydrothieno[3,4-b][1,4]dioxin-5-yl)tin oxadiazole (Compound 6): In a 25 ml double-necked bottle, bromo-7-ethynyl-9,9-dihexyl-9H-fluorene (Compound 4) (0.6 g, 1.3 mmol) and tributyl(2,3-dihydrothieno[3,4-b][1,4]dioxin-5-yl)tin oxadiazole (Compound 5) (2.37 g, 5.5 mmol) were dissolved in toluene (5 ml) under a protective gas atmosphere, and then Pd(PPh3)4 (15 mg) was added. The reaction was carried out at 110°C for 24 hours. After the reaction was completed, the mixture was cooled to room temperature, and then the organic phase was washed with a saturated aqueous solution of potassium fluoride, extracted with dichloromethane, and dried with anhydrous sodium sulfate for 24 hours. The solvent was removed by reduced pressure distillation, and the crude product was purified by column chromatography using silica gel as a filler (petroleum ether: dichloromethane = 4:1). 1HNMR (400MHz, Chloroform-d) δ7.82-7.60 (m, 4H), 7.60-7.29 (m, 3H), 6.36 (d, J = 8.4 Hz, 1H), 4.45-4.16 (m, 5H), 2.04 (dq, J = 23.5, 7.3 Hz, 3H), 1.78-0.48 (m, 36H), 0.12 (s, 6H).

[0077] Tributyl(7-(7-ethynyl-9,9-dihexyl-9H-fluoren-2-yl)-2,3-dihydrothieno[3,4-b][1,4]dioxin-5-yl)stannane (Compound 7): In a 100 mL double-necked bottle, 5-(7-ethynyl-9,9-dihexyl-9H-fluoren-2-yl)-2,3-dihydrothieno[3,4-b][1,4]dioxin-5-yl)stannane (Compound 6) (1 g, 2 mmol) was dissolved in 20 mL of anhydrous tetrahydrofuran under argon protection, and then heated at -78 °C. At ℃, lithium diisopropylamide (LDA) (2.0M, 6mmol) was added dropwise to the reaction system. After stirring at this temperature for 1.5 hours, tributyltin chloride (0.978g, 3mmol) was added, and then the reaction mixture was slowly heated to room temperature and stirred overnight. After the reaction was completed, the mixture was poured into water and extracted twice with ethyl acetate. The organic phase was washed with saturated brine and dried over anhydrous sodium sulfate for 24 hours, and the solvent was removed by reduced pressure distillation. The product can be directly used for the next step without purification.

[0078] (Compound 8): Compound BBT (45 mg, 0.12 mmol Zhengzhou Alpha) and the crude product obtained above (0.3 g, 0.38 mmol) were dissolved in a toluene solution (10 mL) under protective argon conditions, and then Pd(PPh3)4 (1.45 mg) was added, stirred at 110°C for 12 hours, cooled to room temperature, poured into water, extracted twice with ethyl acetate, the organic phase was washed with saturated brine and dried with anhydrous sodium sulfate for 24 hours, and then the solvent was removed by reduced pressure distillation. The crude product was purified by column chromatography using silica gel as filler (petroleum ether: ethyl acetate = 2:1) 1 H NMR(600MHz,Chloroform-d)δ7.81(d,J=7.3Hz,1H),7.74(s,1H),7.68(d,J=7.8Hz,3H),7.5 9(s,1H),7.50(d,J=18.1Hz,4H),6.33(s,1H),4.33(d,J=47.6Hz,5H),2.89(s,2H),1.96(d, J=62.3Hz,7H),1.56-1.40(m,12H),1.36(dt,J=15.3,7.3Hz,4H),1.26(s,4H),1.20-0.99(m ,20H),0.92(s,5H),0.78(d,J=7.3Hz,8H),0.70(d,J=7.5Hz,6H),0.07(s,4H),0.00(s,2H).

[0079] Synthesis of conjugated polymer 1-NP: 1,4-dioxane (5 mL), the above compound (5 mg, 0.00314 mmol), cuprous iodide (2.38 mg, 0.01256 mmol), methoxypolyethylene glycol azide (25.26 mg, 0.01256 mmol) (Mn = 2000) were added to a reaction bottle and stirred overnight at room temperature. The organic solvent was removed by vacuum distillation to form a thin film; then, the resulting mixture was added with 10 ml of ultrapure water to obtain an aqueous solution of nanoparticles by self-assembly; finally, the aqueous solution of the obtained nanoparticles was treated by dialysis (the molecular weight cutoff of the dialysis bag was 3500 kDa) to obtain nanoparticles.

[0080] Figure 1 This is the total composite picture.

[0081] Figure 2 The ultraviolet absorption image (a), infrared absorption image (b), TEM image (c), and particle size image (d) of the obtained nanoparticles 1-NP are respectively.

[0082] Figure 3The photothermal absorption diagram of the prepared nanoparticles. The temperature rise curves of polymer 1-NP when irradiated with 808nm laser with a power of 0.8w at concentrations of 0mg / ml, 2mg / ml, 4mg / ml and 8mg / ml, respectively.

[0083] Example 2: Synthesis of conjugated polymer IEG-NP

[0084] according to Figure 4 Shown is the synthetic route for preparing conjugated polymer IEG-NPs.

[0085] Specific operations include:

[0086] Synthesis of IEG-N3

[0087] In a two-necked bottle filled with nitrogen, the compound IFE-Br2 (see Chinese Patent 202410112003.8) (100 mg, 0.070 mmol) and sodium azide (46 mg, 0.7 mmol) were dissolved in DMF (10 mL), heated at 70 ° C for 3 hours, the reaction was terminated, cooled to room temperature, and then a large amount of water was added and stirred until all the solids were dissolved, then extracted twice with ethyl acetate, and then the organic phase was dried with anhydrous sodium sulfate, and finally the solvent was evaporated in vacuo. The crude product was chromatographed on a silica gel column (petroleum ether: ethyl acetate = 1: 1) to obtain 80 mg of an orange solid with a yield of 89.5%.

[0088] As shown in the figure, HR-MS ESI (m / z) [M+Na]+, compound [C68H74N16O4S3Na]+, theoretical value: 1297.5139, measured value: 1297.5155.

[0089] Synthesis of IEG-NO:

[0090] In a 50mL single-necked round-bottom flask, IEG-N3 (20mg, 0.014mmol) was added, followed by dichloromethane (10mL) to dissolve it, followed by sodium nitrite (6mg, 0.09mmol) and glacial acetic acid (100μL). After stirring at room temperature for 30 minutes, the reactant was poured into water, then extracted twice with ethyl acetate, and finally the organic phase was dried over anhydrous sodium sulfate, and the solvent was removed by distillation under reduced pressure. The crude product was subjected to silica gel column chromatography (petroleum ether: ethyl acetate = 1:1) to obtain 15mg of a blue solid product with a yield of 74.48%.

[0091] Synthesis of IEG-NPs by Reaction of IEG-NO with Diacetylenyl Polyethylene Glycol

[0092] Tetrahydrofuran (5 mL), IEG-NO compound (5 mg, 0.00385 mmol), cuprous iodide (1.82 mg, 0.00962 mmol), diacetylene polyethylene glycol (7.71 mg, 0.00771 mmol) (Mn = 2000) were added to the reaction bottle and stirred at room temperature overnight. The organic solvent was removed by vacuum distillation to form a thin film;

[0093] Subsequently, the obtained mixture was added with 10 ml of ultrapure water to obtain an aqueous solution of nanoparticles by a self-assembly method; finally, the obtained aqueous solution of nanoparticles was treated by a dialysis method (the molecular weight cutoff of the dialysis bag was 3500 kDa) to obtain nanoparticles.

[0094] Figure 4 Synthesis diagram of IEG-NPs.

[0095] Figure 5 They are the ultraviolet absorption graph (a), infrared absorption graph (b), TEM graph (c), particle size graph (d), and photothermal absorption graph of the obtained nanoparticles.

[0096] Figure 6 The photothermal absorption graph of the prepared IEG-NPs is shown in Figure 1. The temperature rise curves of IEG-NPs at concentrations of 0 mg / ml, 0.25 mg / ml, 0.5 mg / ml, and 1 mg / ml when irradiated with a 650 nm laser at a power of 0.8 W.

[0097] Example 3: Synthesis of Conjugated Polymer 3

[0098] according to Figure 7 The synthetic route shown is for the preparation of conjugated polymer 2.

[0099] Synthesis of 5-(9,9-dihexyl-9H-fluorene-2-yl)-2,3-dihydrothiophene[3,4-b][1,4]dioxin (Compound 10): In a 25 ml double-necked bottle, bromo-9,9-dihexyl-9H-fluorene (Compound 9 Aladdin) (1 g, 0.00242 mol) and tributyl(2,3-dihydrothiophene[3,4-b][1,4]dioxin-5-yl)stannane (Compound 5) (4.17 g, 0.00968 mol) were dissolved in toluene (10 ml) under a protective gas atmosphere, and then Pd(PPh3)4 (20 mg) was added. The reaction was carried out at 110°C for 24 hours. After the reaction was completed, the mixture was cooled to room temperature, and then the organic phase was washed with a saturated aqueous solution of potassium fluoride and extracted with dichloromethane. After the organic phase was dried over anhydrous sodium sulfate for 24 hours, the solvent was removed by reduced pressure distillation. Finally, the crude product was purified by column chromatography using silica gel as a filler (petroleum ether: dichloromethane = 2:1). 1HNMR(600MHz,Chloroform-d)δ7.63(dd,J=7.9,1.7Hz,1H),7.56(dd,J=7.9,1.8Hz ,3H),7.24-7.13(m,3H),6.18(s,1H),4.20-4.16(m,2H),4.12-4.08(m,2H),1.94-

[0100] 1.82(m,4H),1.30-1.14(m,2H),1.06-0.89(m,12H),0.80(dt,J=20.7,7 .2Hz,1H),0.65(t,J=7.3Hz,6H),0.62-0.56(m,2H),0.58-0.52(m,1H).

[0101] Tributyl(7-(9,9-dihexyl-9H-fluoren-2-yl)-2,3-dihydrothieno[3,4-b][1,4]dioxin-5-yl)stannane (Compound 11): In a 100 mL double-necked bottle, 5-(9,9-dihexyl-9H-fluoren-2-yl)-2,3-dihydrothieno[3,4-b][1,4]dioxin-5-yl)stannane (Compound 10) (1 g, 2 mmol) was dissolved in 20 mL of anhydrous tetrahydrofuran under argon protection, and then heated at -78 °C. Under an environment, n-butyllithium (2.0M, 6mmol) was added dropwise to the reaction system. After stirring at this temperature for 1.5 hours, tributyltin chloride (0.978g, 3mmol) was added, and the reaction mixture was slowly heated to room temperature and stirred overnight. After the reaction was completed, the mixture was poured into water and extracted twice with ethyl acetate. The organic phase was washed with saturated brine and dried over anhydrous sodium sulfate for 24h, and the solvent was removed by reduced pressure distillation. The product can be directly used for the next step without purification.

[0102] Synthesis of 3,6-bis(5-(7-(9,9-dihexyl-9H-fluorene-2-yl)-2,3-dihydrothieno[3,4-b][1,4]dioxin-5-yl)thiophene-2-yl)-2.5-di(hex-5-yn-1-yl)-2,5-dihydropyrrolo[3,4-c]pyrrole-1,4-dione (Compound 12): Compound DPP (see Chinese Patent No. 202410081757.1) (80 mg , 0.13mmol) and the crude product tributyl (7-(9,9-dihexyl-9H-fluorene-2-yl)-2,3-dihydrothieno [3,4-b] [1,4] dioxin-5-yl) stannane (0.3g, 0.38mmol) obtained above were dissolved in a toluene solution (3mL) under protective argon gas, and then Pd (PPh3) 4 (1.45mg) was added, stirred at 110 ° C for 2 hours, and then stirred at room temperature overnight. The mixture was poured into water and extracted twice with ethyl acetate. The organic phase was washed with saturated brine and dried with anhydrous sodium sulfate for 24 hours, and then the solvent was removed by reduced pressure distillation. The crude product was purified by column chromatography using silica gel as filler (petroleum ether: ethyl acetate = 1:1).

[0103] Synthesis of conjugated polymer 2-NP: Chloroform (5 mL), the above compound (5 mg, 0.00385 mmol), cuprous iodide (1.82 mg, 0.00962 mmol), methoxy polyethylene glycol azide (7.71 mg, 0.00771 mmol) (Mn = 2000) were added to a reaction bottle and stirred overnight at room temperature. The organic solvent was removed by vacuum distillation to form a thin film; then, the resulting mixture was added with 10 ml of ultrapure water to obtain an aqueous solution of nanoparticles by self-assembly; finally, the aqueous solution of the obtained nanoparticles was treated by dialysis (the molecular weight cutoff of the dialysis bag was 3500 kDa) to obtain nanoparticles.

[0104] Figure 7 This is the overall synthesis diagram of conjugated polymer 2-NP.

[0105] Figure 8 The ultraviolet absorption graph (a), infrared absorption graph (b), TEM (c), and particle size graph (d) of the obtained nanoparticles.

[0106] Fig. 9 The photothermal absorption diagram of conjugated polymer 2-NP. The temperature rise curve of conjugated polymer 2-NP when irradiated with 650nm laser with power of 0.8w at concentrations of 0mg / ml, 0.5mg / ml, 1mg / ml and 2mg / ml respectively.

[0107] The present invention has been described in detail above. For those skilled in the art, without departing from the purpose and scope of the present invention, and without the need to carry out unnecessary experimental conditions, the present invention can be implemented in a wide range under equivalent parameters, concentrations and conditions. Although the present invention provides specific embodiments, it should be understood that the present invention can be further improved. In a word, according to the principles of the present invention, the application is intended to include any changes, uses or improvements to the present invention, including departure from the disclosed scope in the application, and changes made with conventional techniques known in the art.

Claims

1. A method for synthesizing an amphiphilic quasi-conjugated molecule, comprising the following steps: copolymerizing a conjugated structure molecule represented by formula I with a hydrophilic macromolecule represented by formula II to obtain a conjugated polymer, i.e., an amphiphilic quasi-conjugated molecule; In Formula I, Any of the following groups: (R is H or C1-C 10 Straight or branched alkyl), is any of the following groups: hydrogen, -N3, -NH2; n = an integer from 1 to 10; m = an integer from 1 to 10; is any one of the following groups: hydrogen, alkynyl, thiol, carboxyl and aldehyde; and Cannot be H at the same time; In formula II, The same as or different from ○, at least one of which is any one of an azido group, an alkynyl group, a thiol group, a carboxyl group and an aldehyde group, and the other can be C1-C 10 Alkoxy group; n represents an integer of 10-50.

2. The method according to claim 1, characterized in that The conjugated structure molecule shown in Formula I is any one of the following compounds:

3. The method according to claim 1, characterized in that The hydrophilic macromolecule represented by formula II is any one of the following compounds:

4. The method according to claim 1, characterized in that: The synthesis method of the amphiphilic quasi-conjugated molecule is as follows: a hydrophilic macromolecule containing an azide group and a conjugated structure molecule containing an alkyne group are subjected to a click reaction; Alternatively, a hydrophilic macromolecule containing an alkyne group is subjected to a click reaction with a conjugated structure molecule containing an azide group to obtain an amphiphilic quasi-conjugated molecule.

5. The method according to claim 4, characterized in that The synthesis method of the amphiphilic quasi-conjugated molecule is as follows: in an inert atmosphere and in the presence of an inorganic salt, a hydrophilic macromolecule containing an azide group and a conjugated structure molecule containing an alkyne group undergo a click reaction. Alternatively, in an inert atmosphere and in the presence of an inorganic salt, a hydrophilic macromolecule containing an alkynyl group undergoes a click reaction with a conjugated structure molecule containing an azide group to obtain an amphiphilic quasi-conjugated molecule.

6. The method according to claim 5, characterized in that The inorganic salt is at least one of cuprous iodide and cuprous bromide; The molar fraction of the hydrophilic macromolecule is 0.075 to 1.5 parts; The molar fraction of the conjugated structure molecule is 0.100 to 0.380; The inorganic salt is fed in an amount of 0.075 to 1.5 parts by mole; The click reaction is carried out at a temperature of 25-80°C and for a time of 24-72 hours.

7. An amphiphilic quasi-conjugated molecule prepared by the method according to any one of claims 1 to 6.

8. The amphiphilic quasi-conjugated molecule according to claim 7, characterized in that The amphiphilic quasi-conjugated molecule is one of the following polymers:

9. Nanoparticles prepared from the amphiphilic quasi-conjugated molecules according to claim 7 or 8.

Citation Information

Patent Citations

  • Molecular fluorophores and preparation method thereof and use for short wavelength infrared imaging

    CN109641921A

  • Single molecular weight fluorene-azobenzene amphiphilic oligomer precursor, oligomer, self-assembled fiber and preparation method

    CN115490716A

  • Synthesis method and function regulation method of amphiphilic conjugated molecule

    CN117843934A

  • Nitric oxide responsive amphiphilic conjugated oligomer and preparation method thereof

    CN117986275A

  • Stimulus-responsive amphiphilic conjugated polymer and preparation method thereof

    CN117986598A